Modelling Polymers as Compressible Elastic Spheres in Couette Flow - Donglin Xie; Dave E. Dunstan (Substantia, 2017)
A model of polymer chains as compressible elastic spheres in flow is presented. The spherical polymer blobs are assumed to compress in simple Couette flow in accord with recent rheo-optic measurements on semi-dilute solutions. The experimentally determined decrease in radius with increasing shear rate is predicted by the model. Furthermore, the model predicts power law exponents for the viscosity-shear rate within the range of measured values for polymer chains.